The Indonesian National Games of 1951 and 1953: Identity, Ethnicity and Gender - Brown, Colin (Asian Studies Association of Australia (ASAA) & Research School of Pacific and Asian Studies (RSPAS), The Australian National University, 2006)
My objective in this paper is to fill out one aspect of the role of sport in Indonesian social history by examining the second and third National Games (Pekan Olahraga Nasional -- PON), one held in 1951 in Jakarta and the other in 1953 in Medan.The primary sources used in this study are the commemorative books produced for each of these Games, recording the main activities associated with them. These books offer useful insights into the state of Indonesian society and politics at the beginning of the 1950s, at a time when the country was working out ways of giving substance to the independence recently won from the Dutch.